Cross-fertilization in Teaching and Learning between Institutions after COVID-19 Shutdown: A Collaborative Effort - Joyce Phikisile Dhlamini; Vivian Thuso Molaodi (Research in Social Sciences and Technology- OpenED Network, 2021)
Research reported in this article investigated the effectiveness of collaborative effort between schools to bridge the existing gaps that erupted during the outbreak of COVID-19. There are gaps in teaching and learning within the previously privileged institutions and the marginalised institutions in South Africa. Such gaps might have a negative impact on how teaching and learning are conducted. The purpose of this article was to investigate the creative and constructive ways of managing the anxiety related to socio-economic impacts in schools, amongst which were the introduction of online teaching and learning technologies, new methodologies and contents. This article is underpinned by the concepts of the establishment of advantageous strategies for collaboration, knowledge sharing and knowledge transfer. Qualitative document analysis has been adopted as a methodology to collect information for this study. The outbreak of COVID-19 has evoked inequalities amongst the communities. However, the re-opening of schools exacerbated multiple challenges. While teaching and learning is the centre of the education project in South Africa, which the country has to adapt to, most institutions were faced with a number of challenges. This study’s major finding revealed that collaboration is synergistic and can bring out the best contribution that might currently perceive partnership within the school system. This article recommends ways of bridging the gap between schools through developing partnerships between institutions through cross-fertilisation.